Zn(0)-Catalysed mild and selective hydrogenation of nitroarenes. Issue 14 (2nd July 2020) - Sun, Shuting; Du, Muyao; Zhao, Ruixiang; Jv, Xinchun; Hu, Pan; Zhang, Qun; Wang, Bo
Abstract : The hydrogenation of nitroarenes is one of the most important strategies for the preparation of anilines. Abstract : The hydrogenation of nitroarenes is one of the most important strategies for the preparation of anilines. However, it is still a great challenge to develop mild and efficient synthetic routes toward aniline synthesis, particularly those employing both non-precious metal catalysts and low-pressure H2 . Herein, we report a highly efficient protocol for the selective hydrogenation of nitroarenes in neutral H2 O using H2 (1 atm) over a heterogeneous Zn(0) catalyst under mild conditions. The nitro groups of an array of nitroarenes can be converted into –NH2 with up to 99% conversions and a selectivity of >99%, even when functionalized with easily reducible substituents, or in the presence of aromatic ketones or styrene. This study might open an avenue for the selective hydrogenation of nitroarenes over a zinc catalyst using 1 atm H2 .